Informal Economy: Definition and Structure - БарсуковаСветлана Юрьевна (Journal of Economic Sociology, 2010)
Informal economy is a leader for the scientific discourse. The number of publications on the topic is growing like a snowball. At the same time the borders of this term remain undefined as well as its internal structure. That fact that this term is well-known let people use it rather easily. But the term has its own history that makes us understand it and correlate with the established traditions. It is obvious that the direct transfer of the definitions and meanings is not a good thing. Informal economy – the term of world science however its conceptualization has a lot of national versions. Scientists from the Western countries underline different qualitative characteristics of informal economic order with comparison to the scientists from the transition countries. This puts a challenging issue of systematization of the approaches to the definition of informal economy and at the same time it puts the task of working out the conceptual scheme of informal economy in Russia.